Metastasis: clinical management and intensive care of cancer pain (Research, Society and Development, 2022)
Pain, like other vital signs, is a very important indicator and can highlight possible complications of the patient's clinical condition. In this regard, pain should be addressed as the fifth vital sign of life and should be evaluated according to the needs and clinical conditions of each patient. In this aspect, palliative care should be especially focused on improving the quality of life of the patient and family members who suffer from metastasis and cancer. For this, care encompasses comprehensive assistance whose benefit is the relief of pain, suffering and other spiritual, physical and emotional problems. Thus, the objective of this study focuses on: Evidencing which clinical management and intensive care can be offered to patients with cancer pain. This research was carried out through an integrative literature review, by collecting data in the scientific databases SCIELO, PUBMED and MDLINE. The results by analyzing the studies indicate that conventional treatments are no longer as effective depending on the stage of metastasis. In advanced cases, the use of oral medication no longer provides the necessary effects, in these cases, it is of paramount importance to search for new relief therapies, with acupuncture techniques, massages, offers of physical activities, needling, pilates and among other procedures. physiotherapeutic treatments that stimulate blood circulation and promote relaxation. Pain management in palliative care must follow the humanization, planning and systematization behaviors of nursing, with interventions based on the patient's clinical needs and particularities.